(untitled) (Journal of the College of Basic Education, 2022)
Ribat originally, residing on the enemy’s jihad in war, and the association of horses and their preparation, then it became other goals such as; To provide places for visitors to the Holy City and its pilgrims to come to it, as one of its objectives has become religious education and some methods such as: Sufism.